Health and Safety Issues in Romanian Forests: Findings from FSC Certification Audits - HALALISAN AURELIU-FLORIN; POPA BOGDAN; BORZ STELIAN ALEXANDRU (FORESTS, 2022)
In a wider context of attempting to minimise forestry related occupational hazards, this paper aimed to evaluate the ability of FSC forest management certification to contribute to identifying,describing, and reducing health and safety issues in forest management in Romania. By extracting and analysing the health and safety related non-conformities from auditing reports issued for Romanian forest management operations between 2013 and 2018, the study reveals that the most important risk factors are organizational factors, followed by equipment-related factors. The correlation of the results with other findings in the forest operations literature indicates that forest management certification is a suitable tool to identify and describe the health and safety aspects of forest management related activities, especially for forest operations. The analysis also indicates some possible causes of the high rate of work accidents in Romanian forestry: obsolete and less mechanised technology, low concern for providing and using specific safety equipment, low wages in forest operations, lack of proper training etc. All these aspects point to the need for improving safe organisational culture.
Keywords: Romanian forestry sector; forest operations; health and safety; risk factors; accident factors; FSC; forest certification; non-conformities